Chronic Pain After Groin Hernia Surgery in Women: A Patient-reported Outcome Study Based on Data From the Swedish Hernia Register. Issue 2 (27th August 2021) - Jakobsson, Ebbe; Lundström, Karl-Johan; Holmberg, Henrik; de la Croix, Hanna; Nordin, Pär
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to evaluate chronic pain 1 year after surgery, and risk factors for chronic pain after groin hernia repair in women. Background: Groin hernia surgery in women is less frequently studied than in men. Chronic pain is common after groin hernia surgery and remains an important area with room for improvement. Previous studies are small or inconclusive. Guidelines recommend timely repair of all female groin hernias. Methods: From the Swedish Hernia Register 4021 female and 37, 542 male patients operated between September 1, 2012 and August 30, 2017 responded to a patient-reported outcome questionnaire (response rate 70.0%) 1 year after primary groin hernia surgery. Multivariable analysis was performed to compare chronic postoperative pain in women with men as a control group, and to evaluate risk factors for chronic pain in women. Results: Among women operated for groin hernia, 18% suffered chronic postoperative pain. The risk for chronic pain was significantly higher for women [odds ratio 1.3 (95% confidence interval 1.16–1.46). Three risk factors for chronic pain in women were found: high body mass index, high American Society of Anesthesiologists classification, and femoral hernia. No differences in chronic pain in women were seen when comparing surgical methods or emergency versus elective surgery. Conclusions: Almost one-fifth of women suffered of chronic pain affecting daily activity after groin hernia repair. Chronic pain was more common for women than men. In view of the high-rate chronic postoperative pain, further research on management strategies in female groin hernia is warranted.